Prostor (a čas) v komunikaci a jeho proměny v souvislostech s vývojem mediačních prostředků - Kořenský, Jan (Slavistična revija, 2014)
Human communication "whose natural" form in direct communication is based on the uniformity of place and time and limited by human physiological abilities - has been developing towards "liberation" from the natural limitations of time and space. The history of changes in human communication is thus the history of the evolution of communication transmission. This evolution starts with the introduction of writing and its consistent distinction between form and substance. With its substance element (stone, clay tablets, papyrus, parchment, paper), writing in the semiotic sense represents the channel and the medium (chemistry and technique of the material element of the writing form). The present stage of this evolution is marked by the dramatic growth of media technologies based on electronic digital computer means. These technologies are connected to the beginning and development of "technological languages" as specific semiotic systems that are part of modern media technologies.
Keywords: communication; communication medium; jezikoslovje; komunikacija; linguistics; media technologies; mediji; medium; technology; tehnologija